2013
DOI: 10.1155/2013/153634
|View full text |Cite
|
Sign up to set email alerts
|

RNA Splicing: A New Player in the DNA Damage Response

Abstract: It is widely accepted that tumorigenesis is a multistep process characterized by the sequential accumulation of genetic alterations. However, the molecular basis of genomic instability in cancer is still partially understood. The observation that hereditary cancers are often characterized by mutations in DNA repair and checkpoint genes suggests that accumulation of DNA damage is a major contributor to the oncogenic transformation. It is therefore of great interest to identify all the cellular pathways that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 131 publications
(144 reference statements)
1
36
0
Order By: Relevance
“…Recognition of the importance of RBPs for the DDR has increased in recent years (Lenzken et al 2013;Dutertre et al 2014;Naro et al 2015;Shkreta and Chabot 2015;Kai 2016). Using differential quantification of the poly(A) + RNA-protein interactome, we identified more than 260 RBPs that displayed increased binding activity to polyadenylated transcripts upon induction of DSBs in cultured human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition of the importance of RBPs for the DDR has increased in recent years (Lenzken et al 2013;Dutertre et al 2014;Naro et al 2015;Shkreta and Chabot 2015;Kai 2016). Using differential quantification of the poly(A) + RNA-protein interactome, we identified more than 260 RBPs that displayed increased binding activity to polyadenylated transcripts upon induction of DSBs in cultured human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The major trans-acting regulators of the RNA lifecycle are RNA-binding proteins (RBPs) whose emerging role has been recognized in many aspects of the DDR (for reviews, see Reinhardt et al 2011;Lenzken et al 2013;Dutertre et al 2014;Naro et al 2015;Shkreta and Chabot 2015;Kai 2016). Several recent large-scale proteomic studies have reported that RNA processing and translation factors are post-translationally modified by DDR signaling (Matsuoka et al 2007;Bennetzen et al 2010;Bensimon et al 2010;Beli et al 2012;Jungmichel et al 2013), and many RBPs are essential for the DDR (Paulsen et al 2009;Adamson et al 2012;Boucas et al 2015).…”
mentioning
confidence: 99%
“…For instance, some mutant p53 proteins can drive breast cancer [88], and the alternative splicing of cyclin D1 mRNA leads to distinct protein forms with opposite activities on cell cycling (G1-S progression inhibition, S-G2/M progression acceleration and apoptosis enhancement or delay) [92,93,94]. In addition, alternative RNA processing has emerged as a new pathway in genome maintenance that affects the expression of protein forms involved in both RNA splicing and genome surveillance [95]. The functions of HLTF truncated forms might act as oncogenic proteins and/or interfere with the normal activities of wt HLTF as dominant negative oncomorphic forms of a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Later DDR stages, involve changes in gene expression. Emerging evidence supports that DNA damage influences not only expression levels of its target genes, by altering transcription rates and mRNA half-life, but also exon selection and ultimately their coding potential 6 .…”
Section: Introductionmentioning
confidence: 99%